Mucoadhesive and Drug Release Properties of Benzocaine Gel: Properties of benzocaine gel - Jelvehgari, Mitra; Rashidi, Mohammad-Reza; Samadi, Hedayte (Iranian Journal of Pharmaceutical Sciences, 2006)
Gel dosage forms are successfully used as drug delivery systems considering their ability to control drug release and to protect medicaments from a hostile environment. The aim of this work was to investigate the properties of carbopol 934P polymeric system in water-misible cosolvents such as glycerin and alcohol. Benzocaine is a local anesthetic and the mucosal gel formulation is applied in the treatment of dental pain. Samples were prepared by simply dispersing different amounts of Carbopols (0.5-3%) into the alcoholic solution at the room temperature and were kept at 4, 25 and 40 °C. All these systems were then characterized for distribution, bioadhesiveness on the mucosa, physical stability and drug release. The silastic membrane was employed. The membrane must not be a barrier for drug transport. Franz diffusion cell used to study in vitro drug release. The increase in carbopol concentration caused increased viscosity and bioadhesiveness. Neutralization of pH in various concentrations of carbopol gels showed resulted in increased viscosity. A relationship between the viscosity and bioadhesive strength was shown in the neutralized carbopol gels. On the other hand, the results indicated that increasing amount of alcohol and glycerin reduced drug release. In contrast, by increasing the amount of water, elasticity and release rate was increased. Vision-gel® was used as a reference for comparison with the oromucosal gel formulation. The results showed that diffusion of benzocaine from oromucosal gel and commercial sample followed Higuchi law.